2016
DOI: 10.1002/eat.22554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation (tDCS) on binge‐eating disorder

Abstract: This proof of concept study is the first to find ameliorating effects of tDCS in BED. Stimulation of the right DLPFC suggests that enhanced cognitive control and/or decreased need for reward may be possible functional mechanisms. The results support investigation of repeated tDCS as a safe and noninvasive treatment adjunct for BED. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2016; 49:930-936).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 34 publications
6
107
1
5
Order By: Relevance
“…Kekic et al found that tDCS reduced food craving more effectively in those with lower vs. greater impulsiveness on a reward-choice task (Kekic et al, 2014), but these were healthy-weight participants. Our lab also found that greater vs. lower intent to restrict calories predicted tDCS suppression of food craving, but these were participants with BED (Burgess et al, 2016). However, both studies hint that greater baseline cognitive control may enhance the anti-obesity actions of tDCS.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Kekic et al found that tDCS reduced food craving more effectively in those with lower vs. greater impulsiveness on a reward-choice task (Kekic et al, 2014), but these were healthy-weight participants. Our lab also found that greater vs. lower intent to restrict calories predicted tDCS suppression of food craving, but these were participants with BED (Burgess et al, 2016). However, both studies hint that greater baseline cognitive control may enhance the anti-obesity actions of tDCS.…”
Section: Introductionmentioning
confidence: 69%
“…Preferred-food consumed was the mean kcal intake of each participant's highest ranked food; less-preferred food consumed was the mean kcal intake of the two lower ranked foods averaged for each participant. The same script, foods, and time period were used in our previous study (Burgess et al, 2016). Eating difference scores were calculated by subtracting kcals eaten with active tDCS from kcals eaten with control tDCS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreases in sweet cravings, total and preferred food intake, desire to binge eat following tDCS in persons with BED have been reported (Burgess et al 2016) however, impulsive tendencies in choice behavior were shown to be less susceptible to the ameliorating effects of tDCS (Kekic et al 2014). Although in the same study, singlesession tDCS has not been effective in lowering food cravings, same group, in a recent study (Kekic et al 2017), also reported transient improvements on the wanting/liking of food and on bulimic behaviors during the 24-hour post-stimulation following three sessions of bilateral tDCS in patients with bulimia nervosa.…”
Section: Neural Stimulation Therapiesmentioning
confidence: 99%